1968
DOI: 10.1007/bf02540171
|View full text |Cite
|
Sign up to set email alerts
|

Elimination of aflatoxins from peanut meal

Abstract: Peanut meal containing aflatoxins was heat treated in the presence of moisture and chemicals to reduce the aflatoxin content. Treatments with ammonia, methylamine, sodium hydroxide and ozone were effective in either destroying afiatoxins or greatly reducing aflatoxin levels as indicated both by TLC analysis and feeding experiments with ducklings and rats. Weight gains for animals receiving the treated meals were essentially comparable to those for animals receiving aflatoxin-free meal. The treated meMs, howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
2

Year Published

1979
1979
2014
2014

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(22 citation statements)
references
References 14 publications
0
20
0
2
Order By: Relevance
“…Oxidizing agents easily attack the double bond in the furo-furan ring of aflatoxins B1 and G1 while the lactone ring common to all aflatoxins is hydrolyzed in aqueous and alkaline environments. Among chemical agents that have been tested, inorganic and organic bases such as ammonia, ethylamine, and methylamine showed to be the most efficacious in degrading aflatoxins (Dollear, Mann, Codifer, Gardner, Koltun & Vix, 1968). Studies have achieved total elimination of aflatoxins by heating with methylamine and sodium hydroxide at 100°C (Mann, Codifer, Gardner, Koltun, & Dollear, 1970).…”
Section: Introductionmentioning
confidence: 99%
“…Oxidizing agents easily attack the double bond in the furo-furan ring of aflatoxins B1 and G1 while the lactone ring common to all aflatoxins is hydrolyzed in aqueous and alkaline environments. Among chemical agents that have been tested, inorganic and organic bases such as ammonia, ethylamine, and methylamine showed to be the most efficacious in degrading aflatoxins (Dollear, Mann, Codifer, Gardner, Koltun & Vix, 1968). Studies have achieved total elimination of aflatoxins by heating with methylamine and sodium hydroxide at 100°C (Mann, Codifer, Gardner, Koltun, & Dollear, 1970).…”
Section: Introductionmentioning
confidence: 99%
“…Maeba et al (1988) reported the destruction and detoxification of AFB 1 and AFG 1 in agricultural products treated with 1.1 ppm of O 3 during 5 minutes [24]. Aflatoxin degradation in different food products, either fresh or processed at different O 3 concentrations, has been reported by some authors [13, 25–28]. An advantage of gaseous O 3 , apart from being a powerful disinfectant, oxidant, and aflatoxins degrader, is that it decomposes quite fast into O 2 and does not have toxic effect [2931].…”
Section: Introductionmentioning
confidence: 99%
“…A large number of chemicals can react with aflatoxins and convert them to less toxic and mutagenic compounds. These chemicals include acids, bases, oxidizing agents, bisulphites and gases [Dollear et al, 1968;Mann et al, 1970;Mendez-Albores, 2007]. The components of the neem tree (Azadirachta indica) is well known for its interference in aflatoxin biosynthesis with very little action on the fungal mycelia [Bhatnagar et al, 1988., Allameh et al, 2001 .…”
Section: Inhibition Of Aflatoxin Biosynthesis and Degredation Of The mentioning
confidence: 99%